1996
DOI: 10.1128/aem.62.12.4542-4547.1996
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of expressed sequence tags of Agaricus bisporus and their assignment to chromosomes

Abstract: The genome of the cultivated basidiomycete Agaricus bisporus Horst U1 and of its homokaryotic parents has been characterized by using an optimized method of pulsed-field gel electrophoresis. Expressed sequence tags obtained as expressed cDNAs from a primordial tissue-derived cDNA library and a number of previously isolated genes were used to identify the individual chromosomes of the parental lines of Horst U1. The genome consists of 13 chromosomes, and its total size is 31 Mb. For those chromosomes that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Other species form the order Agaricales were found to have similar chromosome numbers: e.g. Agaricus bisporus (n = 13, Sonnenberg et al , 1996), Coprinopsis cinerea (n = 13, Muraguchi et al , 2003), Pleurotus ostreatus (n = 11, Larraya et al , 1999) or Laccaria montana (n = 9, Mueller et al , 1993). Given that our genetic map reached marker saturation and covers 93% of the scaffold-level assembly, the presence of additional chromosomes is highly unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Other species form the order Agaricales were found to have similar chromosome numbers: e.g. Agaricus bisporus (n = 13, Sonnenberg et al , 1996), Coprinopsis cinerea (n = 13, Muraguchi et al , 2003), Pleurotus ostreatus (n = 11, Larraya et al , 1999) or Laccaria montana (n = 9, Mueller et al , 1993). Given that our genetic map reached marker saturation and covers 93% of the scaffold-level assembly, the presence of additional chromosomes is highly unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…For rapid isolation of gene markers for the development of a genomic map of A. bisporus (42,47), we partially sequenced a number of cDNA clones from a Horst U1 primordium library and analyzed these sequences by a database search. One of these cDNAs was a 3Ј-truncated cDNA in which an internal XhoI site was fused to vector sequences and which appeared to encode a protein with considerable homology to ⌬ 1 -pyrroline-5-carboxylate dehydrogenases from the yeast Saccharomyces cerevisiae (35) and humans (22), a mitochondrial protein involved in the second step of the conversion of proline to glutamate.…”
Section: Characterization Of the A Bisporus ⌬ 1 -Pyrroline-5-carboxymentioning
confidence: 99%
“…Being of similar lengths, these chromosomes cannot be resolved by CHEF analysis (46). Definite assignment of pruA to chromosome IV was achieved by restriction fragment length polymorphism RFLP analysis of homokaryotic offspring (47).…”
Section: Characterization Of the A Bisporus ⌬ 1 -Pyrroline-5-carboxymentioning
confidence: 99%
“…The earliest cytological study of the bisporus variety by Evans (1959), showed 12 chromosomes in haploids. Furthermore the CHEF (clamped homogeneous electric field) analysis revealed that this variety had 13 chromosomes with a genome size of 31 Mb (Royer et al, 1992;Lodder et al, 1993;Sonnenberg et al, 1996). Observing large groups of non-recombining markers in the linkage studies led to the conclusion that either the CO hardly occurred in large genome regions or that such recombinants cannot germinate successfully, because the germination rate of the spores is low .…”
Section: Molecular Breeding In Two Varieties Of a Bisporusmentioning
confidence: 99%
“…Studies on recombination frequency of this hybrid also indicated that the recombination landscape is likely under genetic control. All constructed linkage maps of the bisporus variety are very short (Summerbell et al, 1989; considering the estimated chromosome number (n=13) of A. bisporus (Sonnenberg et al, 1996). As COs are mainly restricted at the chromosome ends in the bisporus variety, in the offspring of a cross between the individuals of an inter-varietal hybrid and homokaryons of the bisporus variety, COs might shift towards the ends of the chromosome.…”
Section: Introductionmentioning
confidence: 99%